Comparing the Rates of Misconduct Between Private and Public Prisons in Texas - El Sayed, Sarah A. (Crime & delinquency, 2020)
Mass incarceration has led to an increased reliance on private prisons. Yet, there is little evidence regarding the extent to which public safety and misconduct patterns differ across private versus public prisons. Combining data from prisoners in the State of Texas within a counterfactual research design, the current study examines differences in the likelihood of engaging in misconduct among comparable male inmates sentenced to a private over a public prison unit. Findings indicate there are no significant differences in the amount of misconduct committed by inmates in either public or private institutions—with the exception of physical violence. Inmates assigned to private facilities were 10% less likely to engage in institutional violence compared with similarly situated inmates assigned to public facilities.